Changes in self-reported health and wellbeing outcomes in 36,951 primary school children from 2014 to 2022 in Wales: an analysis using annual survey data - Einhorn, Johanna; James, Michaela; Kennedy, Natasha; Marchant, Emily; Brophy, Sinead (Frontiers in Public Health, 2024)
This study examines the changes in childhood self-reported health and wellbeing between 2014 and 2022. An annual survey delivered by HAPPEN-Wales, in collaboration with 500 primary schools, captured self-reported data on physical health, dietary habits, mental health, and overall wellbeing for children aged 8-11 years. The findings reveal a decline in physical health between 2014 and 2022, as evidenced by reduced abilities in swimming and cycling. For example, 68% of children (95%CI: 67%-69%) reported being able to swim 25m in 2022, compared to 85% (95% CI: 83%-87%) in 2018. Additionally, unhealthy eating habits, such as decreased fruit and vegetable consumption and increased consumption of sugary snacks, have become more prevalent. Mental health issues, including emotional and behavioural difficulties, have also increased, with emotional difficulties affecting 13%-15% of children in 2017-2018 and now impacting 29% of children in 2021-2022. Moreover, indicators of wellbeing, autonomy, and competence have declined. Importantly, this trend of declining health and wellbeing predates the onset of the Covid-19 pandemic, suggesting that it is not solely attributed to the pandemic's effects. The health of primary school children has been on a declining trajectory since 2018/2019 and has continued to decline through the COVID recovery period. The study suggests that these trends are unlikely to improve without targeted intervention and policy focus.